Association between heart rhythm and cortical sound processing - Marcomini, Renata S. [UNESP]; Frizzo, Ana Claudia F. [UNESP]; Goes, Viviane B. de [UNESP]; Regacone, Simone F. [UNESP]; Garner, David M.; Raimundo, Rodrigo D.; Oliveira, Fernando R.; Valenti, Vitor E. [UNESP] (Imr Press, 2018)
Sound signal processing signifies an important factor for human conscious communication and it may be assessed through cortical auditory evoked potentials (CAEP). Heart rate variability (HRV) provides information about heart rate autonomic regulation. We investigated the association between resting HRV and CAEP. We evaluated resting HRV in the time and frequency domain and the CAEP components. The subjects remained at rest for 10 minutes for HRV recording, then they performed the CAEP examinations through frequency and duration protocols in both ears. Linear regression indicated that the amplitude of the N2 wave of the CAEP in the left ear (not right ear) was significantly influenced by standard deviation of normal-to-normal RR-intervals (17.7%) and percentage of adjacent RR-intervals with a difference of duration greater than 50 milliseconds (25.3%) time domain HRV indices in the frequency protocol. In the duration protocol and in the left ear the latency of the P2 wave was significantly influenced by low (LF) (20.8%) and high frequency (HF) bands in normalized units (21%) and LF/HF ratio (22.4%) indices of HRV spectral analysis. The latency of the N2 wave was significantly influenced by LF (25.8%), HF (25.9%) and LF/HF (28.8%). In conclusion, we promote the supposition that resting heart rhythm is associated with thalamo-cortical, cortical-cortical and auditory cortex pathways involved with auditory processing in the right hemisphere.
Keywords: Autonomic nervous system; cardiovascular physiology; hearing; neurophysiology; sound; speech